Ställsam : En fristående lösning för elvispar - Sandberg, Elin (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
This project is a thesis for a Bachelor of Science in Industrial Design Engineering at Luleå Tekniska Universitet. In the project, a concept has been developed for a solution to be able to use an electric whisk without holding it. It can be difficult to hold an electric whisk and whisk together a batter. The shoulder aches, you may have reduced strength in the wrist, or you wish it was possible to have your hands free to easily sift down the flour a little at a time. On the market today solutions are sold in the form of stands that comes with a new electric whisk and only fits that electric whisk, or expensive and bulky kitchen assistants. The purpose of the project has been to solve the problem that it is not possible to use the electric whisk you already have at home, without holding it, and to investigate whether it is possible to make the solution universal. The goal of the project has been to develop a concept for a solution that has high usability. The process that has been used in the project is IDEO's user-centered design process, human-centered design, with the three phases inspiration, ideation, and implementation. Each phase has started with a broad exploration, and then limited and analysed the results from the phase before the process started again in the next phase. The result is an electric driven stand for electric whisks that have an included attachment, as well as an included bowl that is rotated using a motor. The stand can be adjusted in height to be easily adapted to different lengths of whisks, and so that the bowl can be removed from the stand, without having to mount off the electric whisk. The maximum height of the stand is high enough for the longest whisks to come above the bowl, and low enough for the electric whisks with the shortest whisks to be used with the stand. The electric whisk is attached to the stand, by gluing a small attachment to the underside of the electric whisk, the attachment is then clicked onto the stand. To avoid having to connect two cables to the wall, there is ...